EMPOWERING DIGITAL MEDIA THROUGH YOUTUBE PLATFORM IN FLIPPED LEARNING - Amaliah, Amaliah (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Learning process, especially during the Covid-19 pandemic requires more complex, flexible, and sustainable life skills competences which in turn requires more effective and empowering digital media of learning. Technological development in the education sector since the Industrial Revolution (IR) 4.0 era has promoted the realization of empowering flipped learning to enhance autonomous English learning process. For this reason, there should be a worldwide platform to help teacher cope with this condition. YouTube is the accessible, and free platform for both students and teacher. It triggers the writer to empower a channel of English learning to be useful for students. This best practice has two purposes: (1) to describe how digital media through YouTube platform in flipped learning empowered, and (2) to explain why digital media through YouTube platform in flipped learning should be empowered. The study was conducted in three months, started from July to September 2020. This study uses qualitative descriptive method particularly to explain the current phenomena. The results show that the YouTube video as digital media empowered in flipped learning using the four stages, identifying (information responsive), pursuing (information active), producing (discovery responsive), and authoring (discovery active). Finally they can create their own content in the form of digital comic. The results also show that teachers should be creative in developing English digital through the YouTube platform empowered in the flipped classrooms due to its 3I (Image, Interactivity, and Integration).